Efficacy of BCG Vaccination Against Respiratory Tract Infections in Older Adults During the Coronavirus Disease 2019 Pandemic. (5th March 2022) - Moorlag, Simone J C F M; Taks, Esther; ten Doesschate, Thijs; van der Vaart, Thomas W; Janssen, Axel B; Müller, Lisa; Ostermann, Philipp; Dijkstra, Helga; Lemmers, Heidi; Simonetti, Elles; Mazur, Marc; Schaal, Heiner; et al.
Abstract: Background: Older age is associated with increased severity and death from respiratory infections, including coronavirus disease 2019 (COVID-19). The tuberculosis BCG vaccine may provide heterologous protection against nontuberculous infections and has been proposed as a potential preventive strategy against COVID-19. Methods: In this multicenter, placebo-controlled trial, we randomly assigned older adults (aged ≥60 years; n = 2014) to intracutaneous vaccination with BCG vaccine (n = 1008) or placebo (n = 1006). The primary end point was the cumulative incidence of respiratory tract infections (RTIs) that required medical intervention, during 12 months of follow-up. Secondary end points included the incidence of COVID-19, and the effect of BCG vaccination on the cellular and humoral immune responses. Results: The cumulative incidence of RTIs requiring medical intervention was 0.029 in the BCG-vaccinated group and 0.024 in the control group (subdistribution hazard ratio, 1.26 [98.2% confidence interval, .65–2.44]). In the BCG vaccine and placebo groups, 51 and 48 individuals, respectively tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with polymerase chain reaction (subdistribution hazard ratio, 1.053 [95% confidence interval, .71–1.56]). No difference was observed in the frequency of adverse events. BCG vaccination was associated with enhanced cytokine responses after influenza, and also partially associated after SARS-CoV-2 stimulation. In patients diagnosed with COVID-19, antibody responses after infection were significantly stronger if the volunteers had previously received BCG vaccine. Conclusions: BCG vaccination had no effect on the incidence of RTIs, including SARS-CoV-2 infection, in older adult volunteers. However, it improved cytokine responses stimulated by influenza and SARS-CoV-2 and induced stronger antibody titers after COVID-19 infection. Clinical trials registration: EU Clinical Trials Register 2020-001591-15 ClinicalTrials.gov NCT04417335. Abstract : BCG vaccination did not protect older adults in a Western European country against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or other respiratory tract infections. However, those subsequently infected with SARS-CoV-2 displayed higher antibody responses against SARS-CoV-2 than nonvaccinated individuals.